An outbreak of hepatitis A associated with salted clams in Busan, Korea - Hyunjin Son; Miyoung Lee; Youngduck Eun; Wonseo Park; Kyounghee Park; Sora Kwon; Seungjin Kim; Changhoon Kim (Epidemiology and Health, 2021)
OBJECTIVES In July 2019, there were multiple reports on patients with hepatitis A among the visitors of a restaurant in Busan. The current study presents the results of an epidemiological investigation and outlines the supplementary measures that would help with hepatitis A control. METHODS A cohort study was conducted for all 2,865 customers who visited restaurant A from June to July. Using a standardized questionnaire, participants reported the presence of hepatitis A symptoms and whether they had consumed any of 19 food items. As for participants who had visited public health centers, their specimens were collected. RESULTS From the study cohort, 155 participants (5.4%) had confirmed hepatitis A. The epidemic curve was unimodal, and the median number of days from the restaurant visit to symptom onset was 31 days. A genotype analysis indicated that 89 of 90 tested patients had hepatitis A virus (HAV) genotype 1A. The results of a multivariate logistic regression analysis indicated that the ingestion of salted clams increased the risk of hepatitis A by 68.12 times (95% confidence interval [CI], 9.22 to 510.87). In an unopened package of salted clams found and secured through traceback investigation, HAV genotype 1A was detected. CONCLUSIONS To prevent people from ingesting uncooked clams, there needs to be more efforts to publicize the dangers of uncooked clams; the food sampling test standards for salted clams should also be expanded. Furthermore, a laboratory surveillance system based on molecular genetics should be established to detect outbreaks earlier.